2021
DOI: 10.1186/s12992-020-00655-3
|View full text |Cite
|
Sign up to set email alerts
|

Immigration, perceived discrimination and mental health: evidence from Venezuelan population living in Peru

Abstract: Background The association between international migration and mental health is conditioned to several factors, and discrimination may play a significant role. Currently, Peru is one of the principal Venezuelan migrant-receiving countries in Latin America. There are around one million Venezuelan refugees and migrants in the country. This study evaluates the association between self-perceived discrimination and mental health problems in Venezuelan population living in Peru. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 46 publications
2
22
0
2
Order By: Relevance
“…Finally, this study contributes to the nascent but growing research on Venezuelan migrants’ psychological well-being. Previous studies found that Venezuelan immigrants experience psychological distress due to societal discrimination [ 61 , 62 , 63 , 64 ], fears about education and career status loss in the destination country [ 65 ], and the COVID-19 pandemic in general [ 23 ]. Moreover, there is evidence that Venezuelans in Peru experience stress when unable to send remittances during the pandemic [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study contributes to the nascent but growing research on Venezuelan migrants’ psychological well-being. Previous studies found that Venezuelan immigrants experience psychological distress due to societal discrimination [ 61 , 62 , 63 , 64 ], fears about education and career status loss in the destination country [ 65 ], and the COVID-19 pandemic in general [ 23 ]. Moreover, there is evidence that Venezuelans in Peru experience stress when unable to send remittances during the pandemic [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, lower level of Perceived Discrimination was significantly linked to refugees' higher orientation towards Colombians and higher reports of psychological adjustment. Ingroup bias and outgroup prejudice in host societies, are pervasive features of human attitudes and have been studied extensively (Mougenot et al, 2021). According to prior research, among Venezuelan refugees in Peru, there was a strong association between reports of perceived discrimination and mental health problems (Mougenot et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Ingroup bias and outgroup prejudice in host societies, are pervasive features of human attitudes and have been studied extensively (Mougenot et al, 2021). According to prior research, among Venezuelan refugees in Peru, there was a strong association between reports of perceived discrimination and mental health problems (Mougenot et al, 2021). In a study examining Iranian refugees in the Netherlands, it was found that perceived discrimination was positively linked to negative psychological and sociocultural outcomes including negative affect, subjective feelings of linguistic incompetence and lower levels of overall well-being (Lindert et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Moreover, once the Venezuelan migration in Peru became noticeable, migrants might have encountered an increasing wave of xenophobia and discrimination. 30,31 Thus, beyond the burden of HIV stigma, Venezuelan PLWH might have faced xenophobia and negative context reception, 32 which directly affect their mental health 33,34 and hamper linkage to health services and retention in care. In this context, it is possible that, through a snowball effect, migrant PLWH could share information about certain HIV health services as "safer places" for peers.…”
Section: Discussionmentioning
confidence: 99%